Extraction of Turmeric Leaves (Curcuma longa L.) as a Natural Preservative for Tuna Fish Using Ultrasound-Assisted Extraction (UAE) Method - Salma, Isni Salma Salsabillah; Rossi Agnessi Pebriana; Bekti Palupi; Ditta Kharisma Yolanda Putri; Istiqomah Rahmawati (Journal of Biobased Chemicals, 2024)
Turmeric leaves (Curcuma longa L.) contain phytochemical compounds that can be utilized as natural food preservatives or bioformalin due to its antibacterial properties. The extraction method used in this study is Ultrasound-Assisted Extraction (UAE), with the aim to determine the effect of variable sample-solvent ratio, time, and particle size on total flavonoid, tannin, and alkaloid compounds, as well as to determine the optimal shelf life of fresh tuna. This study used sample-solvent ratio variables of 1:10, 1:15, and 1:20; time variables of 10, 20, and 30 minutes; and particle size variables of 60, 80, and 100 mesh. The highest total flavonoid compound was obtained in the variable sample-solvent ratio of 1:20, particle size of 100 mesh, and time of 20 minutes at 98,076 mg/L. The highest total tannin compound was obtained in the variable sample-solvent ratio of 1:15, particle size of 60 mesh, and time of 10 minutes at 41,697 mg/L. The highest total alkaloid compound was obtained in the variable sample-solvent ratio of 1:10, particle size of 100 mesh, and time of 20 minutes at 10,092 mg/L. The optimum curing time for tuna is 36 hours at room temperature with variable sample-solvent ratio, time, and particle size of 1:20 g/mL, 20 minutes, and 100 mesh with 20% concentration. The running has the highest flavonoid compounds, so it can be concluded that flavonoid compounds have a major effect on the preservation process of tuna.